Augustus as Princeps Senatus - Markelov, Andrei Y. (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Octavian took the title of princeps senatus during the first lectio senatus of his long reign. The article deals with the role of the title of princeps of the Senate in the system of government under Augustus. I argue that the first Roman Emperor attached importance to his position of the princeps senatus not only in the context of the First settlement but during his whole long reign. The Emperor was eager to highlight the overall importance of this post. Moreover, he defined his place in the Senate with this position and it had functional significance for him during sessions of the consilium publicum. The restoration of the title of princeps senatus took place in a new circumstance. The reality of the epoch led to some transformations in the title’s functionality.